Anisotropic polarization fatigue in Bi3.15Nd0.85Ti3O12 thin films. (13th April 2016) - Yang, Feng; Guo, Yichen; Li, Luyan; Tang, Minghua
Abstract: The origin of polarization fatigue is one of the most important long-standing problems in ferroelectric studies. In bismuth-layered Aurivillius ferroelectrics, no consensus between fatigue models and experimental results has been reached. In this study, polarization fatigue in Bi3.15 Nd0.85 Ti3 O12 was investigated using polycrystalline thin films with different orientations. We demonstrated that polarization fatigue strongly depends on film orientation. The (1 0 0)pc films are vulnerable to fatigue, (0 0 l )pc films are fatigue-resistant, whereas (1 1 7)pc films show moderate fatigue behaviour. Our analysis suggests that the physical mechanisms responsible for the fatigue-free phenomenon in (0 0 l )pc films, the low-frequency fatigue phenomenon in (1 0 0)pc films, and slow fatigue in (1 1 7)pc films were bismuth-layered structures, space charge accumulation, and domain wall pinning, respectively. This study provides a reference for understanding electric fatigue and its anisotropy in bismuth-layered ferroelectric films.